2008
DOI: 10.1111/j.1348-0421.2008.00009.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of splenic Gr‐1int immature myeloid cells in tumor‐bearing mice

Abstract: Itis known thatthenumber of ImC, expressing myeloid markers, CD11b and Gr-1, increase with tumor growth and ImC play a role in the escape of tumor cells from immunosurveillance in tumor-bearing mice and cancer patients. However, the mechanisms by which ImC suppress immune responses in tumor-bearing mice have not been completely elucidated. In the present study, we investigated the function of splenic ImC freshly isolated from tumor-bearing mice and splenic ImC differentiated in vitro by GM-CSF. Freshly isolate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 19 publications
2
22
0
Order By: Relevance
“…ϩ cells into antigen-presenting cells agrees with other results in tumor-bearing mice (73) and polymicrobial sepsis (19). This ex vivo preference appears to be due to the action of GM-CSF, and the cells do not survive in culture without the growth factor.…”
Section: Cd11bsupporting
confidence: 79%
“…ϩ cells into antigen-presenting cells agrees with other results in tumor-bearing mice (73) and polymicrobial sepsis (19). This ex vivo preference appears to be due to the action of GM-CSF, and the cells do not survive in culture without the growth factor.…”
Section: Cd11bsupporting
confidence: 79%
“…In other models it was observed that the accumulation of CD11b + Gr-1 + in the spleen has been associated with tumor development. Yamamoto et al [19] evaluated CD11b + Gr-1 + expression in splenocytes of the BALB/c mice inoculated with colon carcinoma and sarcoma cell lines by the time the tumors reached 10 mm in diameter. It was found that the naive BALB/c mice presented 4.4% of CD11b + Gr-1 + in the spleen whereas tumor-bearing mice expressed more than 11% of this suppressor cell marker.…”
Section: Discussionmentioning
confidence: 99%
“…These two subpopulations diVer in their potential to suppress T-cell responses [14]. The application of Ly-6C-and Ly-6G-speciWc antibodies revealed two diVerent subpopulations of MDSC in spleens of tumor-bearing mice: CD11b + Ly6G + Ly6C low MDSC morphologically resembling polymorphonuclear granulocytes (PMN-MDSC) and CD11b + Ly6G -Ly6C high MDSC with monocytic phenotype (MO-MDSC) [15].…”
Section: Mdsc Surface Markers and Subsetsmentioning
confidence: 99%